To investigate techniques for the design of FIR filters - Thaint Thaint, Khine (2015)
Design and investigation of Finite Impulse Response (FIR) filter design techniques are explored using Window method and Least Square method in this report. Different approaches and techniques for many types of FIR filter designs are studied. The advantages and drawbacks of different design techniques are compared. Studies and researches are carried out in order to perform tasks in FORTRAN and Matlab. Comparisons of different design methods are presented. Windowing method and Least Square method were completed in FORTRAN for FIR filter design. To overcome the main weakness of Least Square method, which is occurring maximum error at band edge, the alternative Weighted Least Square method is introduced. This Weighted Least Square is applied to study the optimum values of equiripple in both passband and stopband. Two proposed design techniques were implemented in Microsoft Visual Studio 2005 in order to find coefficient values and Matlab platform to plot the frequency response.